VD_FINDINFO HC / 2021 / 346 vom 20. April 2021 - VD Tribunal cantonal (2021)
ASSISTANCE JUDICIAIRE, REJET DE LA DEMANDE, DROIT D'ÊTRE ENTENDU, AVOCAT D'OFFICE | 117 let. a CPC (CH), 118 al. 1 let. c CPC (CH)